2018
DOI: 10.1002/ecs2.2478
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of water, nutrients, and microclimate on leaf litter mass loss in headwater riparian forests

Abstract: Leaf litter decomposition is an essential function in forest ecosystems, and riparian areas may contribute to faster rates of litter mass loss due to higher moisture and nutrient levels in riparian than upland soils. We experimentally tested whether mass loss of red alder leaf litter was (1) greater closer to the stream than further away and (2) increased by nutrient and water additions in riparian habitat near four headwater streams in southwestern British Columbia. We set up blocks of nine transects extendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…It has been further suggested that plant community composition can be related to microbial biomass (Stefanowicz et al 2021) and diversity (Smith & Peay 2021). Studies examining among-site variability in microbial communities or decomposition rates in boreal riparian habitats suggest that soil organic matter content associated to wetland elevation affects microbial abundances (Moon et al 2016) and that decomposition rates (Ramey and Richardson, 2018) can be determined by soil hydrology (but see also Hough andCole 2009, Ramey et al, 2020). In general, soil pH and fertility are the main determinants of microbial community composition (Pennanen et al 1999, Kaiser et al 2016, Zeng et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…It has been further suggested that plant community composition can be related to microbial biomass (Stefanowicz et al 2021) and diversity (Smith & Peay 2021). Studies examining among-site variability in microbial communities or decomposition rates in boreal riparian habitats suggest that soil organic matter content associated to wetland elevation affects microbial abundances (Moon et al 2016) and that decomposition rates (Ramey and Richardson, 2018) can be determined by soil hydrology (but see also Hough andCole 2009, Ramey et al, 2020). In general, soil pH and fertility are the main determinants of microbial community composition (Pennanen et al 1999, Kaiser et al 2016, Zeng et al 2016.…”
Section: Introductionmentioning
confidence: 99%